A method for measuring first glymphatic influx of a cerebrospinal fluid tracer in the human brain - Pripp, Are Hugo; Ringstad, Geir; Valnes, Lars Magnus; Eide, Per Kristian (Frontiers in Neuroscience, 2025)
IntroductionThe glymphatic system is a brain-wide perivascular transport route for fluids and solutes in which cerebrospinal fluid (CSF) serves as a conduit for solute transport and clearance of brain waste. Intrathecal contrast-enhanced magnetic resonance imaging (MRI), where the intrathecal contrast agent serves as a CSF tracer, has been developed to measure glymphatic function in humans. The normalized MRI T1 signal is a semiquantitative measure of CSF flow and exchange with the brain. Objective: To estimate first-time tracer appearance within brain tissue after intrathecal tracer injection.MethodsThis study implemented segmented regression analysis to estimate the first-time tracer appearance of an intrathecal tracer within brain tissues. An increase (breakpoint) in the normalized MRI T1 signal was defined to represent first glymphatic influx of the tracer. The study included 30 reference (REF) subjects with no identified CSF disturbance and 15 patients with a diagnosis of idiopathic intracranial hypertension (IIH). We developed and evaluated the method in REF subjects and further compared it between the two study groups.ResultsThe time to initial glymphatic tracer enrichment in the REF cohort was approximately 1 h in the frontal, temporal, parietal, and occipital cerebral cortex and ranged from two to 4 h in the corresponding white matter regions. In subcortical limbic structures and basal ganglia structures, it was 0.6 and 2.2 h, respectively. Compared with REF subjects, IIH patients presented a non-significant mean difference in the first appearance of ±0.5 h in the cerebral cortex and white matter regions, with somewhat longer estimated delays in the parietal and insular white matter regions. The results are presented as time series plots and estimates with 95% confidence intervals. Additionally, we provide supplementary R code, which can be adapted for use in future studies, and outline a basic assessment of true versus estimated breakpoints using simulated data.ConclusionSegmented regression was found feasible to quantify the time to first glymphatic enrichment, i.e., increase in the normalized MRI T1 signal. Moreover, the method seems reasonable to differentiate first glymphatic influx between the cohorts.